Motion Detection Using Passive Infrared Sensor - Gan, Boon Boon (UTeM, 2011)
This project is about the motion detection using Infra-Red sensor. This project is aim to build a sensor system which is transmit and receive the signal in wirelessly. Besides that, it also acted as an auto power switching system. When the sensor is triggered, the signal will transmit wirelessly to take further action. For this project, I will relate this sensor system with an auto power light switching system. Which mean when the sensor is triggered, light in a room will automatically switch ON. In order to transmit signal wirelessly, this project will used radio frequency module to transmit the signal. For the controller circuit part, this project will use Programmable Interface Controller (PIC) to control the circuit, because it is cheaper and easier to program. The objective of this project is tending to switch ON the light automatically and fan based on the temperature. Besides that, signal transmit wirelessly can avoid the circuit malfunction because of wire broken. After done some research from the internet and advice from the lecturer, tools and equipment are identified to completing the project. Current temperature will shows on a LCD display.